DEVELOPMENT OF A SMART DOLL PROTOTYPE FOR EARLY AGE CHILDREN COLOURS LEARNING IN THREE LANGUAGES - Kurniastuti, Irine; Widiarti, Anastasia Rita; Nugroho, Robertus Adi; Pinaryanto, Kartono (Sanata Dharma University Yogyakarta, 2022)
Early childhood is a golden age to learn a language, not only the mother tongue but also a second or third language. However, learning media that can be used to attract children's interest in learning multi-language is still limited. Therefore, this study aims to develop a smart doll that attracts children to learn Javanese, English, and Indonesian. In particular, this media is intended to help children recognise colours in three languages. This research is developmental research with the following steps: First, collecting information about the product being developed, conducting a literature review and interviewing teachers and parents. Second, planning product design in accordance with the results of the needs analysis. Third, developing the initial product form. Fourth, conducting a preliminary field test on 3 children. Fifth, revising the main product. Sixth, field testing on eight children. Seventh, evaluate the testing result for the next development plan. The result of this research is a prototype of a smart doll that is able to recognize colours in 3 languages. Based on the field trials results, the prototype of this smart doll can attract children’s enthusiasm for learning colours and improve their ability to recognise colours in three languages. Some things that need to be improved will be discussed further.